2020
DOI: 10.1155/2020/7217906
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Neovascularization Secondary to Central Serous Chorioretinopathy: OCT Angiography Findings and Risk Factors

Abstract: Purpose. To identify the clinical characteristics and risk factors for secondary choroidal neovascularization (CNV) in central serous chorioretinopathy (CSC). Methods. In this retrospective study, we included a total of 108 eyes in 106 CSC patients. Group A was defined as patients initially diagnosed with CSC who developed secondary CNV, and group B was defined as patients who did not develop secondary CNV. Clinical and demographic characteristics, optical coherence tomography (OCT) findings at CSC diagnosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…Additionally, we found that vascularized FIPED was wider than avascular FIPED in chronic CSC, which is consistent with the findings of previous studies ( 3 , 5 , 7 , 27 ). Furthermore, the SFCT, thickness of the choriocapillaris layer, and thickness of Haller's layer under FIPED areas were larger in the vascularized FIPED group than in the age-matched avascular FIPED group, but the differences were not significant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, we found that vascularized FIPED was wider than avascular FIPED in chronic CSC, which is consistent with the findings of previous studies ( 3 , 5 , 7 , 27 ). Furthermore, the SFCT, thickness of the choriocapillaris layer, and thickness of Haller's layer under FIPED areas were larger in the vascularized FIPED group than in the age-matched avascular FIPED group, but the differences were not significant.…”
Section: Discussionsupporting
confidence: 93%
“…The choroidal thickness decreases with aging (30). In previous studies, age was found to be an independent risk factor for CNV secondary to chronic CSC, and the mean age of CNV patients was significantly greater than that of non-CNV patients (7,27,31). Therefore, CNV eyes with CSC often show a decreased choroidal thickness.…”
Section: Discussionmentioning
confidence: 94%
“…65 Wider base of PED may also be an indicator of a future CNV in cases of CSC. 85 In contrast to shallow irregular PED of PNV, OCT features in PCV are thumb like or sharp peaked polyp with a tomographic notch in the PED, a hyporeflective lumen surrounded by hyperreflective halo and DLS. ICGA is considered as the gold standard in diagnosis of PCV/AT1N, 86 but structural OCT has been shown to be very helpful in differentiating the pachychoroid spectrum diseases, although they share common choroidal features.…”
Section: Pnv Versus Pachychoroid Spectrum Diseasesmentioning
confidence: 95%
“…e risk factors associated with CNV development include older age, larger PDT spot size, and lesser SFCT [120]. Wider PED and the recurrence of CSCR are also postulated to be risk factors of secondary CNV development [121]. Nonetheless, Chen et al reported CSCR eyes with CNV identified posttreatment could have a stable clinical course of up to 3 years, with SRF only being observed in 17% of eyes after 3 years [122].…”
Section: Relationship Between Choroidal Neovascularization and Central Serous Chorioretinopathymentioning
confidence: 99%